THE INFLUENCE OF EXPERIENTIAL MARKETING AND PERCEIVED VALUE ON SPOTIFY PREMIUM SUBSCRIPTION DECISIONS - Tindatu, Chintya Julia; Saerang, David Paul Elia; Tumiwa, Johan Reineer (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2025)
As music streaming becomes an integral part of daily life, Spotify stands out by offering both free and premium services. While Premium provides ad-free listening, offline downloads, and higher audio quality, many users still choose the free version. This study examines how experiential marketing and perceived value influence the decision of Generation Z in Manado to subscribe to Spotify Premium. Using a quantitative approach, data were collected from 102 respondents through questionnaires and analyzed with multiple linear regression. The results show that both experiential marketing and perceived value have a positive impact, individually and simultaneously, on purchase decisions. These findings emphasize that memorable user experiences and strong perceived benefits encourage Generation Z to upgrade from free to premium services. This research contributes to the understanding of digital subscription behavior and provides practical insights for companies in developing effective marketing strategies.   Keywords: Experiential Marketing, Perceived Value, Purchase Decision